Design, development, and evaluation of terbutaline sulfate sublingual tablets - Yadav, Prof. Narendra (Asian Journal of Pharmaceutics (AJP), 2015)
Terbutaline sulphate is a selective B2 bronchodilator which is used in the treatment of asthma. Conventional TerbutalineÂ tablets available in the market are not suitable where quick onset of action is required. Terbutaline sulphate sublingualÂ tablets were prepared by using mannitol, microcrystalline cellulose pH102 (F1) and lactose monohydrate, microcrystallineÂ cellulose pH102 (F4) as filler and its combination in different ratio, Crospovidone as superdisintegrant and sodium laurylÂ Sulphate as permeability enhancers by drug dispersion direct compression method.The formulation F1 found the 93.51%Â of % drug permeability, 8 seconds disintegration time and 96.95% drug release within one minute.The formulation F4 alsoÂ found the 98.25% of drug permeability, 13 seconds disintegration time and 90.31% drug release within one minute. It wasÂ concluded that the sublingual tablet of Terbutaline sulphate can be formulated for sublingual absorption of drug in emergencyÂ treatment of asthma by Mannitol and Microcrystalline cellulose pH 102 in combination (75% and 25% respectively) or lactoseÂ monohydrate and Microcrystalline cellulose pH 102 in combination (75% and 25% respectively) as filler, Crospovidone asÂ superdisintegrant, and Sodium Lauryl sulphate as permeability enhancer by direct compression drug dispersion method. Key words: Dispersion method, drug permeability, sublingual, superdisintegrant